A CONCEPTUAL STUDY ON MULTIDIMENSIONAL EVALUATION OF LMS PLATFORM IN HEI’S USING BALANCE SCORECARD ON UNDERGRADUATE LEARNERS PERSPECTIVE - Kassim, Umi Kalsom; Phuah, Kit Teng (2018)
The enhancement of technology has introduced new methods of how learning can be interactive and acceptable between the Gen Z populations. Students now are slowly transforming into the enhancement of this usage of E-Learning or virtual learning in their learning process. E-learning has improved the engagement between the lecturers and students to be more prominent and this automatically increasing the independent level among the students. However, even though there are study done on e-learning’s characteristics and effectiveness, hence there are lack of study done to analyze at which level is the effectiveness has given an impact towards student’s perception as shareholders. The primary research of the study is to perceive the effectiveness of E-learning focused on assessment for learning. In the management perspective, this study analyzes how the management can implement E-learning as the medium of delivering in higher education institutions. In order to carry out the research study, a balanced scorecard (BSC) will be designed to identify at which level did the effectiveness and the management of the e-learning to be reviewed. The population of the study are the students randomly selected from public and private universities in Malaysia. Qualitative method used to conduct in depth interview towards the respondents using Nvivo. Structured questionnaire designed to analyze the Conceptual Path Model of Unified Theory of Acceptance and Use of Technology (UTAUT). These models referred in enhancing in developing the balanced scorecard. The analysis done using Reliability analysis, Descriptive analysis, Exploratory Factor Analysis, and Structural Equation Method (SEM) using AMOS. The expected results will provide valuable information for the management staff in managing E-learning strategically and develop value for the students in their charismatic career development.